ANALISA PENGARUH PRICE EARNING RATIO DAN EARNING PER SHARE PADA HARGA SAHAM INDUSTRI MAKANAN DAN MINUMAN (STUDI KASUS DI BURSA EFEK SURABAYA) (Equilibrium: Jurnal Ekonomi-Manajemen-Akuntansi, 2005)
The objective of this research is the effect of Price Earning Ratio Variable and Earning Per Share Variable as determinant of Stock Price in food and baverage firm. Data in this study are food and baverage firm listed on the Surabaya stock exchange. The result of research that Price Earning Ratio variable and Earning Per Share variable significantly related as determinant of stock price in food and baverage firm (F a = 39,247 > F t = 3,59). The result of research that Earning Per Share the dominate as determinant of stock price in food and baverage firm (t a = 8,851 > t t = 2,110) and by in probability < 5 % that is 0, 00.